Tingkat Pengetahuan Ibu Tentang Gizi Balita di Wilayah Kerja Puskesmas Sungai Tabuk 1 - Amelia Dwiana Putri; Ika Friscila; Desilestia Dwi Salmarini; Marini, Elysa Marini (Pusat Riset dan Inovasi Nasional, 2024)
Background: Fulfillment of nutrition for children should be carried out not only from birth but from the time the child is still in the womb. According to the Ministry of Health, stunting is a condition where the body and brain fail to grow due to malnutrition for a long time. So the child is shorter than normal children of his age and has obstacles in thinking. With this incident, it is clear that the nutritional intake provided by children will influence or have an impact on the child's growth and development. Purpose: To determine the level of knowledge of mothers regarding toddler nutrition in the Working Area of ​​Sungai Tabuk Community Health Center 1, Sungai Tabuk Village, City Rt 01, Banjar Regency Methods: The type of research used in this research is pre-experimental research with a one-group pretest-posttest design, that is, cause and effect relationships will be revealed by involving one group of subjects who are observed before the intervention is carried out, then observed again after the intervention. Results: The results of the pretest filling out the questionnaire before education was carried out on the mother's level of knowledge about toddler nutrition. Of the total 15 respondents, there were 11 respondents (73.3%) who had a poor level of knowledge, and there were 4 respondents (26.7%) who had a good level of knowledge. From the total of 15 respondents, there were 2 respondents (13.4%) who had a poor level of knowledge, and there were 13 respondents (86.6%) who had a good level of knowledge, so it can be concluded that there is an increase in knowledge before and after being given education Conclusion: The conclusion shows that there are differences in results before being given education and after being given education